2017
DOI: 10.2147/ijnrd.s135271
|View full text |Cite
|
Sign up to set email alerts
|

Urinary TIMP2·IGFBP7 for the prediction of platinum-induced acute renal injury

Abstract: Introduction: Platinum-based chemotherapy (PBC) is a potent antineoplastic treatment, but cisplatin nephrotoxicity is often the limiting factor. Identifying the patients who are at risk for developing platinum-induced renal injury is an important issue. We tested urinary TIMP2·IGFBP7, a new US Food and Drug Administration (FDA)-cleared test to assess the risk of acute kidney injury (AKI), in a cohort of patients with malignant neoplastic disease receiving PBC. Patients and methods: A total of 58 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…However, in another study, urinary [TIMP2] x [IGFBP7] was found to be a useful tool for early identification of patients who are at risk for cisplatin-induced AKI. 142 In this study, urine samples were collected before cisplatin injection and 12 hours after the end of chemotherapy. Four patients out of 58 developed AKI within 72 hours.…”
Section: Timp2 and Igfbp7mentioning
confidence: 99%
“…However, in another study, urinary [TIMP2] x [IGFBP7] was found to be a useful tool for early identification of patients who are at risk for cisplatin-induced AKI. 142 In this study, urine samples were collected before cisplatin injection and 12 hours after the end of chemotherapy. Four patients out of 58 developed AKI within 72 hours.…”
Section: Timp2 and Igfbp7mentioning
confidence: 99%
“…The intended use of NephroCheckV R is for the clinical risk assessment for moderate to severe AKI within the next 12 h specifically in ICU patients (at least 21 years of age) who have or have had acute cardiovascular and/or respiratory compromise within the past 24 h. There has been interest in assessing the utility of NephroCheckV R for other causes of AKI including drug-induced toxicity. In one clinical study, 4 of 32 patients receiving cisplatin developed AKI, and the AUC-ROC value for TIMP2ÂIGFBP7 was 0.92 within 72 h. 73 However, another study that measured the two biomarkers individually found that there was no change in IGFBP7 concentrations 24 h after cisplatin administration, whereas a 1.1-fold increase in TIMP2 levels could be observed. 71 While 13 patients developed AKI in this study, the AUC-ROC value for the product of TIMP2ÂIGFBP7 was only 0.46 at 24 h. A third study of 46 patients also showed no significant changes from baseline for either TIMP2 or IGFBP7 as well as for TIMP2ÂIGFBP7 at days 3 and 10 after cisplatin treatment.…”
Section: Calbindinmentioning
confidence: 99%
“…Others have previously tested TIMP2xIGFBP7 in a variety of pathologies leading to AKI including e.g. cardiac surgery, major non-cardiac surgery, transcatheter aortic valve implantation (TAVI), critical illness, heart failure and platinum-based chemotherapy and have showed rather consistent results [ 17 , 18 , 20 , 22 , 23 , 32 ]. Thus, current recommendations suggest (TIMP-2) x (IGFBP7) testing in different patient cohorts irrespective of po-AKI-etiology [ 16 ], as performed in this study.…”
Section: Discussionmentioning
confidence: 99%